Simulated Microgravity, Indole-3-Acetyl Acid, and Cow Dung influence on Zea Mays Plant Growth in Contaminated Soil - Amenze Ovenseri; Akinyemi, O. Ogunkeyede,; A.A. Adebayo; P. Tawari-Fufeyin,; Alex Orukpe,; Uche. C. Udeochu (Applied Environmental Research, 2024)
This study investigated the effects of simulated microgravity, indole-3-acetic acid (IAA), and cow dung on Zea mays L. plants growing in soil contaminated with crude oil. Crude oil contamination affects plants negatively in morphology and physiology. For simulated microgravity exposure, IAA introduced and non-IAA introduced seeds of Zea mays L. were grown in a clinostat for 4days before taken to the nursery for planting. IAA was introduced to the seed by soaking in IAA solution for 90 minutes after which it was introduced to the microgravity stimulator (clinostat). After 14 days in the nursery, the seedlings were taken to the field with different concentration of crude oil contaminants and cowdung augmentation. Plant height and chlorophyll index were measured biweekly with a meter rule and chlorophyll meter respectively. Plant biomass (root and shoot) were measured at the termination of the experiment. The results showed that the addition of cow dung significantly improved plant height in treatment microgravity exposed in conta-minated soil with IAA and cow dung (MGGHCDCS). The highest root-shoot biomass value was obtained in treatment non-microgravity exposed in contaminated soil with IAA and cow dung (NMGGHCD), closely followed by treatment non-microgravity exposed Zea mays with IAA growth hormone and cow dung augmentation (NMGHCD), and treatment MG had the lowest value. For 5% crude oil contamination, treatment NMGHCD had the highest root biomass and the lowest root biomass value obtained. This study suggests that combining the three treatments can improve plant morphology in contaminated soil. The improper germination of plants in crude oil contaminated soil will be adequately and successfully addressed by the employment of three combination treatments.